2022
DOI: 10.1038/s41598-022-16986-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole structural reconstruction and quantification of epidermal innervation through the suction blister method and skin-clearing technique

Abstract: Three-dimensional (3-D) analysis of intraepidermal nerve fibers (IENFs) is conducted to advance assessment methods for peripheral neuropathies and pruritic skin disorders. The skin-clearing technique was proven to be a reliable method for 3-D imaging of IENFs. Nonetheless, it still requires further improvement in the imaging process. The aim of this study was to standardize the 3-D evaluation method of IENFs and to suggest promising 3-D biomarkers for clinical application. A total of nine healthy individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The present study demonstrated that the majority of IENFs in the mouse plantar epidermis did not branch. In humans, IENFs exhibit substantial branching, especially in the young, and this structure simplifies with age, suggesting that the degree of nerve fiber branching may also be an indicator of neuropathy [21] . However, in our young adult mice, the IENFs were sparsely branched, and the pattern was clearly different from that of humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated that the majority of IENFs in the mouse plantar epidermis did not branch. In humans, IENFs exhibit substantial branching, especially in the young, and this structure simplifies with age, suggesting that the degree of nerve fiber branching may also be an indicator of neuropathy [21] . However, in our young adult mice, the IENFs were sparsely branched, and the pattern was clearly different from that of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the conventional two-dimensional (2D) analysis method using tissue sections has limitations in analytical accuracy, and a new method for more precise quantification is needed. To address this issue, a 3D analysis method for the IENF density using skin biopsies has been proposed in humans, and its usefulness has been demonstrated [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%